دور اللجنة الدولية للصليب الأحمر في تطبيق القانون الدولي الإنسان - الطاوس صيد; نور الهدى حفصي (My University, 2020)
Summary : The ICRC is a leading humanitarian non-governmental organization tn the humanitarian field , where they contributed since in the inception, it has contributed to the codification of the rules of international humanitrian law and its development it was entrusted with the task of protecting and assisting victims in armed conflicts throught the four geneva conventions of 1949 and their additional protocols of 1977. Also the ICRC aims to promote and disseminate international humanitrian law in the intertional community by applying it to the ground by establishing a basic relationship trust throught the humanitarian diplomatic in addition to providing humanitarian aids and aiding victims the ICRC also seeks to incroporate international law into national legislation and support for the national red crescent and red cross societies in its publication and implementation. ,,,,,,,,,,,,,,,,,,,,,, الملخص : تعتبر اللجنة الدولية للصليب الأحمر منظمة إنسانية غير حكومية رائدة في المجال الإنساني، حيث ساهمت منذ نشأتها على تدوين قواعد القانون الدولي الإنساني وتطويره، وأسندت إليها مهمة حماية و مساعدة ضحايا النازعات المسلحة من خلال اتفاقيات جنيف الأربع لعام 1949 وبروتوكوليها الإضافيين لعام 1977 ، كما تهدف اللجنة الدولية للصليب الأحمر إلى ترقية ونشر القانون الدولي الإنساني من خلال تطبيقه على أرض الواقع عن طريق إقامة علاقات دبلوماسية أساسها الثقة وكذا تقديم المساعدات الإنسانية وإغاثة الضحايا كما تسعى اللجنة لإدراج القانون الدولي في التشريعات الوطنية ودعم الجمعيات الوطنية للهلال الأحمر والصليب الأحمر في نشره وتنفيذها, ,,,,,,,,,,,,,,,,,,,,,,,, Résumé : Le CICR est l’une des principales ONG humanitaires de droit international humanitaire ", où, depuis sa création, il a contribué à la codification et au développement des règles du droit international humanitaire, Mandaté pour protéger et assister les victimes de conflits armés par le biais des quatre Conventions de Genève de 1949 et de leurs Protocoles additionnels de 1977, Le CICR a pour objectif de promouvoir et de diffuser le droit international humanitaire à travers son application sur le terrain par l’établissement de relations diplomatiques fiables, l’assistance humanitaire et le secours aux victimes. Le CICR cherche également à intégrer le droit international dans la législation nationale et à soutenir les sociétés nationales du Croissant-Rouge dans la publication et la mise en œuvre.